Comprehensive Comparisons of Two and Three Dimensional Numerical Estimation of Stress Intensity Factors and Crack propagation in Linear Elastic Analysis - Alshoaibi, Abdulnaser Mohammed (International Journal of Integrated Engineering, 2019)
This paper presents a comprehensive comparison of two finite element software in two and three dimensions. The first is a two-dimensional crack growth simulation program developed as source code by using Visual Fortran Language whereas the second is ANSYS mechanical program (3D structural analysis for fracture mechanic analysis). The procedure consists of computing stress intensity factors (SIFs), the crack growth path and the stresses and strain distributions via an incremental analysis of the crack extension, considering two and three-dimensional analysis. Comparisons between these two software were performed for different case studies for stress intensity factors as well as crack growth trajectory. This source code includes the mesh generator based on the advancing front method as well as all the pre and post process for the crack growth simulation under linear elastic fracture mechanics theory with a user-friendly interface. The maximum circumferential stress criterion was used for prediction of the crack growth in isotropic materials under mixed-mode loading. Furthermore, the equivalent domain integral method has been used for calculating the stress intensity factors values during crack growth. Verification of the predicted crack path and stress intensity factors values were validated with relevant experimental data and numerical results obtained by other researchers with a good agreement.